Tunable Intracrystal Cavity in Tungsten Bronze‐Like Bimetallic Oxides for Electrochromic Energy Storage (Adv. Energy Mater. 5/2022). Issue 5 (3rd February 2022) - Cai, Guofa; Zhu, Rui; Liu, Shiyou; Wang, Jinhui; Wei, Congyuan; Griffith, Kent J.; Jia, Yu; Lee, Pooi See
Abstract : Electrochromic Energy Storage In article number 2103106, Guofa Cai, Pooi See Lee and co‐workers report that Nb18 W16 O93 nanomaterials with superstructure motifs show fast Li + intercalation–deintercalation kinetics and robust stability for both electrochromic and rechargeable energy storage applications. A complementary smart window is further fabricated based on the Nb18 W16 O93 film, which can dynamically regulate the sunlight and solar radiant heat input of buildings while electrical energy can be stored in the smart window, providing a multifunctional system consisting of electrochromism, energy storage and an indicator.